Enuresis Associated with Sleep Disordered Breathing in Children with Sickle Cell Anemia - Lehmann, Gloria C. (2012)
PURPOSE: Enuresis and sleep disordered breathing are common among children with sickle cell anemia. We evaluated whether enuresis is associated with sleep disordered breathing in children with sickle cell anemia. MATERIALS AND METHODS: Baseline data were used from a multicenter prospective cohort study of 221 unselected children with sickle cell anemia. A questionnaire was used to evaluate, by parental report during the previous month, the presence of enuresis and its severity. Overnight polysomnography was used to determine the presence of sleep disordered breathing by the number of obstructive apneas and/or hypopneas per hour of sleep. Logistic and ordinal regression models were used to evaluate the association of sleep disordered breathing and enuresis. RESULTS: The mean age of participants was 10.1 years (median 10.0, range 4 to 19). Enuresis occurred in 38.9% of participants and was significantly associated with an obstructive apnea-hypopnea index of 2 or more per hour after adjusting for age and gender (OR 2.19; 95% CI 1.09, 4.40; p = 0.03). Enuresis severity was associated with obstructive apneas and hypopneas with 3% or more desaturation 2 or more times per hour with and without habitual snoring (OR 3.23; 95% CI 1.53, 6.81; p = 0.001 and OR 2.07; 95% CI 1.09, 3.92; p = 0.03, respectively). CONCLUSIONS: In this unselected group of children with sickle cell anemia, sleep disordered breathing was associated with enuresis. Results of this study support that children with sickle cell anemia who present with enuresis should be evaluated by a pulmonologist for sleep disordered breathing.